Crop resources : proceedings of the 17th annual meeting of the Society for Economic Botany, the University of Illinois, Urbana, June 13-17, 1976 - Seigler, David S. (Academic Press, 1977)
Crop Resources contains papers that were originally presented as a symposium on Crop Resources at the 17th Annual Meeting of the Society for Economic Botany in Urbana, Illinois, 13-17 June 1976. The volume attempts to evaluate (a) the possible nonfood uses of cultivated plants; (b) the extent to which new and additional food resources may become available; (c) the prospects of several specialized uses of plants such as drugs, insecticides, rubber, and condiments; and (d) the origin of four major crops of the American Midwest and prospects for their future development. The discussions include t.